A mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal and its preparation method and application
By doping Ho3+, Pr3+, Ca2+, Mg2+, and Zr4+ ions in the gadolinium gallium garnet crystal, the problem of high infrared laser output threshold and low efficiency in the Ho3+ doped laser crystal is solved, and the efficiency and power improvement of the mid-infrared laser output is achieved.
Patent Information
- Application Number
- CN202411640322.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing Ho3+ doped laser crystals have problems with high threshold, low output power and low efficiency in the output of mid-infrared lasers of 2.7~3.1μm. This is mainly because the fluorescence life of the energy level 5I7 under the laser of Ho3+ is relatively long, which is prone to self-termination effect.
Gadolinium garnet crystal (Gd3Ga5O12) is used as the matrix crystal, combined with Ho3+ as the activation ion, Pr3+ as the deactivated ion of Ho3+, and Ca2+, Mg2+ and Zr4+ are introduced as auxiliary ions. Through the optimization of the doping concentration of these ions, the crystal structure distortion and disorder increase are promoted, thereby non-uniformly broadening of the 2.7~3.1μm fluorescence spectrum band of Ho3+, reducing the fluorescence lifetime of the energy level under the laser, and suppressing the self-termination effect.
It effectively reduces the 2.7~3.1μm mid-infrared laser threshold of Ho3+, improves the laser output efficiency and power, and promotes the output of mid-infrared tuning lasers and ultra-short pulse lasers.
Smart Images

Figure CN119145054B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of single crystal or uniform polycrystalline materials with a certain structure, and in particular to a mid-infrared holmium, praseodymium, calcium, magnesium and zirconium co-doped gadolinium gallium garnet laser crystal and a preparation method and application thereof. Background Art
[0002] 2.7~3.1μm mid-infrared laser is in the strong absorption band of water molecules, and the intrinsic absorption peaks of various gas molecules and atoms are also located in this band. Therefore, 2.7~3.1μm mid-infrared laser is widely used in biomedicine, environmental monitoring, optical remote sensing, nonlinear optics and other fields. In addition, 2.7~3.1μm mid-infrared laser can also be used as a pump source for infrared optical parametric oscillators to obtain 3~5μm and 8~14μm mid-infrared and far-infrared laser outputs, and it also has important applications in space communications, laser radar, optoelectronic countermeasures and other fields. Based on these important applications, rare earth-doped laser crystals that achieve laser output in this band (2.7~3.1μm) are an important research direction.
[0003] The study found that rare earth ions Er 3+ pass 4 I 11 / 2 → 4 I 13 / 2 The radiation transition of Er can achieve 2.7~3μm mid-infrared laser output. 3+ , Ho 3+ The doping concentration of 2.7~3.1μm laser is low and cross relaxation is not easy to occur. 3+ pass 5 I6→ 5 The energy level transition of I7 has a relatively wide fluorescence emission band in the 2.7~3.1μm band, which can not only realize the mid-infrared laser output in the 2.7~3.1μm band, but also facilitate the generation of broadband tuning and ultrashort pulse lasers. 3+ The development of mid-infrared lasers in the 2.7~3.1μm band has been slow due to the shortage of pump sources.
[0004] In recent years, the development of 1150nm lasers has become mature, and its emission wavelength is similar to Ho 3+ The absorption peak of Ho 3+ The pump source of the doped laser gain material. However, Ho 3+ The laser lower energy level 5 The fluorescence lifetime of I7 is long, which is prone to self-termination effect, which is not conducive to the inversion of the number of particles between the upper and lower energy levels of the laser. 3+ The lasing threshold of the mid-infrared laser crystal for ion activation is high, and the laser output power and efficiency are low. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal, comprising a matrix crystal, activation ions, deactivation ions and auxiliary ions;
[0008] The matrix crystal is a gadolinium gallium garnet crystal (chemical formula is Gd3Ga5O 12 ), the activation ion is Ho 3+ , the deactivating ion is Pr 3+ , the auxiliary ions include at least Ca 2+ Mg 2+ and Zr 4+ ; the Pr 3+ The doping concentration is ≥0.05at%.
[0009] Laser crystals are usually composed of activated ions and matrix crystals. The activated ions determine the laser performance of the laser working material, and the matrix crystals determine the physicochemical properties of the laser working material. The interaction between the matrix crystals and the activated ions affects the laser performance of the laser crystal. The present invention uses gadolinium gallium garnet crystals as the matrix crystals and Ho 3+ As the activating ion, it is combined with a variety of specific auxiliary ions (Ca 2+ Mg 2+ and Zr 4+ ) combined to promote the distortion of the crystal structure and increase the disorder, thus making Ho 3+ The 2.7~3.1μm fluorescence band is non-uniformly broadened, making it easier to achieve mid-infrared tunable laser and ultrashort pulse laser output; 3+ As the activating ion Ho 3+ The deactivated ions, while maintaining Ho 3+ Laser upper level 5 While increasing the fluorescence lifetime of I6, it effectively reduces Ho 3+ Laser lower energy level 5 The fluorescence lifetime of I7 is effectively suppressed, thus effectively inhibiting the self-termination effect and reducing Ho 3+ The 2.7~3.1μm mid-infrared laser threshold can be reduced, and the laser output efficiency and power can be improved.
[0010] As a preferred embodiment of the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal of the present invention, the Ho 3+ The doping concentration of Ho is 0.1-5 at%. Optionally,3+ The doping concentration of can be specifically in the range of 0.1at%, 0.5at%, 1at%, 1.5at%, 2at%, 2.5at%, 3at%, 3.5at%, 4at%, 4.5at%, 5at% or any two of them. 3+ It not only enables the mid-infrared holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium, gallium, garnet laser crystal to have strong mid-infrared fluorescence emission, but also effectively avoids the fluorescence emission quenching caused by concentration.
[0011] As a preferred embodiment of the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal of the present invention, the Pr 3+ The doping concentration of Pr is 0.05-0.3at%. Optionally, 3+ The doping concentration of Pr can be specifically in the range of 0.05at%, 0.1at%, 0.15at%, 0.2at%, 0.25at%, 0.3at% or any two of them. 3+ In the case of the activated ion Ho 3+ Can play a deactivation role to effectively reduce the activation ion Ho 3+ The energy level of 2.7~3.1μm laser ( 5 I7) life, it can also better maintain its laser upper energy level ( 5 I6) lifespan, thus facilitating energy storage at the upper level of 2.7~3.1μm laser.
[0012] As a preferred embodiment of the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal of the present invention, the Ca 2+ The doping concentration is 0.1~20at;
[0013] And / or, the Mg 2+ The doping concentration is 0.1~10at;
[0014] and / or, the Zr 4+ The doping concentration is 0.1~20at%.
[0015] The study found that the above doping concentration of Ca 2+ or Mg 2+ Not only can it be used with Zr 4+ The synergistic effect causes the fluorescence spectrum in the mid-infrared band to be non-uniformly broadened, while having little impact on the optical quality of the mid-infrared holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium, gallium, garnet laser crystal.
[0016] Optionally, the Ca 2+The doping concentration of Mg may specifically be in the range of one or any two of 0.1at%, 0.5at%, 1at%, 3at%, 5at%, 7at%, 9at%, 11at%, 13at%, 15at%, 18at%, and 20at%. 2+ The doping concentration of Zr can be specifically in the range of one or any two of 0.1at%, 0.5at%, 1at%, 2at%, 3at%, 4at%, 5at%, 6at%, 7at%, 8at%, 9at%, and 10at%. 4+ The doping concentration can specifically be a range value of one or any two of 0.1at%, 0.5at%, 1at%, 3at%, 5at%, 7at%, 9at%, 11at%, 13at%, 15at%, 18at%, and 20at%.
[0017] As a preferred embodiment of the mid-infrared holmium, praseodymium, calcium, magnesium, zirconium, co-doped gadolinium, gallium, garnet laser crystal of the present invention, the chemical formula of the mid-infrared holmium, praseodymium, calcium, magnesium, zirconium, co-doped gadolinium, gallium, garnet laser crystal is (Ho m Pr n Ca x G 1-m-n-x )3(Mg y Zr z Ga 1-y-z )5O 12 , where m=0.001~0.05, n=0.0005~0.003, x=0.001~0.2, y=0.001~0.1, z=0.001~0.2, 3x+5y=5z.
[0018] Optionally, m may be 0.01, 0.03, or 0.05, n may be 0.0015, 0.002, or 0.003, x may be 0.10, 0.15, or 0.2, y may be 0.0375, 0.05625, or 0.075, and z may be 0.0975, 0.14625, or 0.195.
[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal, comprising the following steps:
[0020] S1. Compounds containing Ho, Pr, Ca, Mg, Zr, Gd and Ga are used as raw materials, mixed evenly and then prepared by a high temperature solid phase method or a liquid phase method to obtain a polycrystalline raw material of holmium, praseodymium, calcium, magnesium and zirconium co-doped gadolinium gallium garnet;
[0021] S2, melting the holmium, praseodymium, calcium, magnesium and zirconium co-doped gadolinium gallium garnet polycrystalline raw material in S1, and then adopting a melt crystal growth process to obtain a mid-infrared laser crystal;
[0022] S3, annealing the mid-infrared laser crystal in S2, and then processing and preparing a mid-infrared holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium, gallium, garnet laser crystal sample for spectroscopy and laser experiments.
[0023] In the above preparation method, in order to compensate for the volatilization of Ga during the crystal growth process, the amount of Ga added is 1~4wt% in excess; the high-temperature solid phase method includes the steps of pressing the mixed raw materials into shape, high-temperature sintering, etc., and the liquid phase method is a coprecipitation method or a sol-gel method.
[0024] Specifically, the melt crystal growth process is one of the following: Czochralski method, crucible descent method, temperature gradient method, flame melting method, guided mold method, cold crucible method, floating zone method, micro-pull-down method, and pedestal method.
[0025] As a preferred embodiment of the preparation method of the present invention, the Ho-containing compound in step S1 is at least one of Ho2O3, Ho(NO3)3, and Ho2(CO3)3;
[0026] The Pr-containing compound is Pr6O 11 , Pr(NO3)3, Pr2(CO3)3;
[0027] The Ca-containing compound is at least one of CaO, Ca(NO3)2, and CaCO3;
[0028] The Mg-containing compound is at least one of MgO, Mg(NO3)2, and MgCO3;
[0029] The Zr-containing compound is at least one of ZrO2, Zr(NO3)4, and Zr(CO3)2;
[0030] The Gd-containing compound is at least one of Gd2O3, Gd(NO3)3, and Gd2(CO3)3;
[0031] The Ga-containing compound is at least one of Ga2O3, Ga(NO3)3, and Ga2(CO3)3.
[0032] As a preferred embodiment of the preparation method of the present invention, the sintering temperature of the high temperature solid phase method in step S1 is 1350~1500°C, and the sintering time is 36~60h. Preferably, the rate of heating or cooling in the high temperature solid phase method is 0.5~3°C / min, more preferably 1~2°C / min. Optionally, the sintering temperature of the high temperature solid phase method can be specifically 1350°C, 1400°C, 1450°C, 1500°C, and the sintering time can be specifically 36h, 42h, 48h, 54h, 60h.
[0033] As a preferred embodiment of the preparation method of the present invention, the temperature of the annealing treatment in step S3 is 1200~1450℃, and the time is 60~72h. Specifically, the atmosphere of the annealing treatment is air, and the heating or cooling rate is 0.5~2℃ / min. Optionally, the temperature of the annealing treatment can be specifically 1200℃, 1250℃, 1300℃, 1350℃, 1400℃, 1450℃, and the time can be specifically 60h, 62h, 64h, 66h, 68h, 70h, 72h.
[0034] In the third aspect, the present invention provides an application of the above-mentioned mid-infrared holmium, praseodymium, calcium, magnesium, zirconium, co-doped gadolinium, gallium, garnet laser crystal, which is used to achieve 2.7-3.1 μm mid-infrared laser output. Mid-infrared lasers in this band have important applications in biomedicine, environmental monitoring, optical remote sensing or nonlinear optics.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention uses gadolinium gallium garnet crystal as the matrix crystal and Ho 3+ As the activating ion, it is combined with a variety of specific auxiliary ions (Ca 2+ Mg 2+ and Zr 4+ ) combined to promote the distortion of the crystal structure and increase the disorder, thus making Ho 3+ The 2.7~3.1μm fluorescence band is non-uniformly broadened, making it easier to achieve mid-infrared tunable laser and ultrashort pulse laser output; 3+ As the activating ion Ho 3+ The deactivated ions, while maintaining Ho 3+ Laser upper level 5 I6 fluorescence lifetime can also reduce Ho 3+ Laser lower energy level 5 The fluorescence lifetime of I7 is effectively suppressed, thus effectively inhibiting the self-termination effect and reducing Ho 3+ The 2.7~3.1μm mid-infrared laser threshold can be reduced, and the laser output efficiency and power can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Room temperature mid-infrared fluorescence spectra of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal of Example 1 and the holmium-praseodymium co-doped gadolinium-gallium-garnet laser crystal of Comparative Example 4;
[0038] Figure 2 The laser upper energy level corresponding to the 1206nm fluorescence emission of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (a) of Example 1 and the holmium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (b) of Comparative Example 1 5I6 Lifetime spectrum;
[0039] Figure 3 The laser lower energy level corresponding to the 2060nm fluorescence emission of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (a) of Example 1 and the holmium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (b) of Comparative Example 1 is shown in FIG. 5 I7 lifetime spectrum. DETAILED DESCRIPTION
[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0041] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0042] Examples 1 to 3 and Comparative Examples 1 to 6
[0043] Table 1 Components and doping concentrations in various embodiments and comparative examples
[0044]
[0045] The chemical formula of the matrix crystal GGG in Table 1 is Gd3Ga5O 12 The chemical formula of the matrix crystal YAG is Y3Al5O 12 .
[0046] The preparation method of the above-mentioned holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (polycrystalline powder) comprises the following steps:
[0047] S1. According to the stoichiometric ratio of each element in the chemical formula in Table 1, weigh Ho2O3, Pr6O 11 , CaO, Gd2O3, Ga2O3, MgO and ZrO2, after being uniformly mixed, a polycrystalline raw material was prepared by a high temperature solid phase method (sintering at 1450℃ for 48h), and then ground again in an agate mortar to obtain a polycrystalline powder;
[0048] S2, melt the polycrystalline raw material in S1 by induction heating, and then use the oriented GGG crystal as the seed crystal, <111> Direction growth, according to the melt pulling method crystal growth process (rotation rate of 2rpm, pulling speed of 1.5mm / h, crystal cooling rate of 30℃ / h) to obtain a laser crystal with a diameter of 25mm and an equal diameter length of about 40mm;
[0049] S3, subjecting the laser crystal in S2 to high temperature annealing treatment (air atmosphere, annealing temperature of 1400°C, annealing time of 72h, heating and cooling rate of 1°C / min) to obtain a holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium, gallium, garnet laser crystal.
[0050] The preparation method of the above-mentioned holmium, praseodymium, calcium, magnesium and zirconium co-doped yttrium aluminum garnet laser crystal (polycrystalline powder) comprises the following steps:
[0051] S1. According to the stoichiometric ratio of each element in the chemical formula in Table 1, weigh Ho2O3, Pr6O 11 , CaO, Y2O3, Al2O3, MgO and ZrO2 were mixed evenly and then prepared into polycrystalline raw materials by high temperature solid phase method (sintering at 1500℃ for 48 h), and then ground again in an agate mortar to obtain polycrystalline powder;
[0052] S2, melt the polycrystalline raw material in S1 by induction heating, and then use oriented YAG crystal as seed crystal to heat the polycrystalline raw material in S1. <111> Direction growth, according to the melt pulling method crystal growth process (rotation rate of 6rpm, pulling speed of 1mm / h, crystal cooling rate of 30℃ / h) to obtain a laser crystal with a diameter of 25mm and an equal diameter length of about 40mm;
[0053] S3. The laser crystal in S2 is subjected to high temperature annealing treatment (air atmosphere, annealing temperature of 1450°C, annealing time of 72h, heating and cooling rate of 1°C / min) to obtain a holmium, praseodymium, calcium, magnesium, zirconium co-doped yttrium aluminum garnet laser crystal.
[0054] Performance Testing
[0055] 1) Fluorescence spectrum test
[0056] Test method: Using 1150 nm Raman fiber laser as the excitation source, the FLSP-920 fluorescence spectrometer produced by Edingurgh Company of the United Kingdom tested the room temperature fluorescence spectra of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (polycrystalline powder) of Example 1 and the holmium-praseodymium-co-doped gadolinium-gallium-garnet laser crystal (polycrystalline powder) of Comparative Example 4, in the range of 2750-3100 nm. The test results are as follows: Figure 1 shown.
[0057] according to Figure 1 It can be concluded that the room temperature fluorescence spectrum of the holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium gallium garnet laser crystal (Ho, Pr: SGGG) of Example 1 is compared with the room temperature fluorescence spectrum of the holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium gallium garnet laser crystal (Ho, Pr: GGG) of Comparative Example 4. The fluorescence peak near 2.83 μm shows an obvious non-uniform broadening. The half-width (FWHM) of the 2.83 μm fluorescence peak of the holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium gallium garnet laser crystal (Ho, Pr: SGGG) of Example 1 is about 51 nm, while the half-width (FWHM) of the 2.83 μm fluorescence peak of the holmium, praseodymium, calcium, magnesium, zirconium co-doped gadolinium gallium garnet laser crystal (Ho, Pr: GGG) of Comparative Example 4 is only about 39 nm. The wide fluorescence emission band is conducive to the realization of mid-infrared tunable laser and ultrashort pulse laser output, and also shows that the co-doped auxiliary ion (Ca2+ Mg 2+ and Zr 4+ ) after the crystal structure is distorted and disorder increases.
[0058] 2) Fluorescence lifetime test
[0059] Test method: Opolette-355I optical parametric oscillator (OPO) laser was used as the excitation source, and the decay curve was tested in transient mode of fluorescence spectrometer. The OPO pulse frequency was 2 Hz, and the monitoring wavelength was 1206 nm (corresponding to 5 I6→ 5 I8 transition) and 2060nm (corresponding to 5 I7→ 5 I8 transition), the laser upper energy level corresponding to the 1206nm fluorescence emission of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (polycrystalline powder) and the holmium-praseodymium-calcium-magnesium-zirconium co-doped yttrium-aluminum-garnet laser crystal (polycrystalline powder) was fitted. 5 I6 lifetime spectrum and laser lower energy level corresponding to 2060 nm fluorescence emission 5 I7 life spectrum, test results are as follows Figure 2 , Figure 3 And as shown in Table 2.
[0060] according to Figure 2 and 3 It can be seen that the 2.7-3.1 μm laser upper energy level of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal (Ho,Pr:SGGG) in Example 1 is 5 I6 and laser lower energy level 5 The lifetimes of I7 are 0.47ms and 2.76ms respectively. At the same time, combined with the laser upper energy level of the holmium calcium magnesium zirconium co-doped gadolinium gallium garnet laser crystal (Ho:SGGG) in comparative example 1 5 I6 and laser lower energy level 5 The lifetime of I7 (0.48ms, 7.77ms) shows that the deactivated ion Pr 3+ Successfully incorporated into the matrix, effectively evacuating the Ho 3 + The number of particles on the 2.7~3.1μm laser lower energy level reduces the fluorescence lifetime of the laser lower energy level, but has little effect on the fluorescence lifetime of the laser upper energy level, effectively suppressing the Ho 3+ The self-termination effect of luminescence near 3μm is beneficial to reduce Ho 3+ The output threshold of 2.7~3.1μm laser is improved, and the laser output power and efficiency are increased.
[0061] Table 2 Fluorescence lifetime in each embodiment and comparative example
[0062]
[0063] According to the data in Table 2, the laser upper energy level of the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystals of Examples 1 to 3 is 5 The fluorescence lifetime of I6 reaches 0.42~0.47ms, and the energy level under the laser 5 The I7 fluorescence lifetime reaches 1.32-2.76 ms, and the ratio of the laser lower energy level to the laser upper energy level lifetime reaches 3.14-5.87, indicating that the holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal of the present invention maintains Ho 3+ Laser upper level 5 I6 fluorescence lifetime, while effectively reducing Ho 3+ Laser lower energy level 5 The fluorescence lifetime of I7 is reduced, thereby reducing the Ho 3+ The 2.7~3.1μm mid-infrared laser threshold can be reduced, thereby improving the laser output efficiency and power.
[0064] According to Comparative Example 1, 3+ As a deactivating ion, it can reduce Ho 3+ Laser lower energy level 5 I7 fluorescence lifetime; at the same time, according to Comparative Examples 2, 3 and 4, it can be found that only Ca 2+ Mg 2+ and Zr 4+ Combined with auxiliary ions, it can maintain Ho 3+ Laser upper level 5 The fluorescence lifetime of I6 is effectively reduced while Ho 3+ Laser lower energy level 5 The fluorescence lifetime of I7, Ho 3+ The lifetime ratio of the lower energy level of the 2.7~3.1μm laser to the upper energy level of the laser is small; in addition, according to Comparative Example 5, it can be seen that the use of other matrix crystals (YAG) instead of gadolinium gallium garnet crystals (GGG) and the activation ion Ho 3+ , deactivated ion Pr 3+ and auxiliary ions (Ca 2+ Mg 2+ and Zr 4+ ) can also reduce Ho 3+ Laser lower energy level 5 The fluorescence lifetime of I7 will also lead to the 3+ Laser upper level 5 The fluorescence lifetime of I6 is greatly reduced, making it difficult to improve the laser output efficiency and power. According to Comparative Example 6, it can be found that when Pr 3+ When the doping concentration is too low, it is difficult to effectively reduce the laser energy level. 5 The life of I7 cannot reduce the laser threshold and improve the laser output efficiency and power.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal, characterized in that: It is composed of matrix crystals, activating ions, deactivating ions and auxiliary ions; The matrix crystal is a gadolinium gallium garnet crystal, and the activation ion is Ho 3+ , the deactivating ion is Pr 3+ , the auxiliary ions include at least Ca 2+ Mg 2+ and Zr 4+ ; The Ho 3+ The doping concentration of Pr 3+ The doping concentration is 0.05~0.3at; The Ca 2+ The doping concentration is 0.1 to 11 at% or 15 to 20 at%, and the Mg 2+ The doping concentration of Zr is 0.1~4at% or 7~10at%. 4+ The doping concentration is 0.1~11 at% or 15~20 at%.
2. The mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal according to claim 1, characterized in that: The chemical formula of the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal is (Ho m Pr n Ca x G 1-m-n-x )3(Mg y Zr z Ga 1-y-z )5O 12 , where m=0.001~0.05, n=0.0005~0.003, x=0.001~0.11 or 0.15~0.2, y=0.001~0.04 or 0.07~0.1, z=0.001~0.11 or 0.15~0.
2.
3. The method for preparing the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal according to claim 1 or 2, characterized in that: The following steps are involved: S1. Compounds containing Ho, Pr, Ca, Mg, Zr, Gd and Ga are used as raw materials, and after being uniformly mixed, a high-temperature solid phase method or a liquid phase method is used to prepare a polycrystalline raw material of holmium, praseodymium, calcium, magnesium and zirconium co-doped gadolinium gallium garnet; S2, melting the holmium, praseodymium, calcium, magnesium and zirconium co-doped gadolinium gallium garnet polycrystalline raw material in S1, and then adopting a melt crystal growth process to obtain a laser crystal; S3, annealing the laser crystal in S2.
4. The preparation method according to claim 3, characterized in that: The Ho-containing compound in step S1 is at least one of Ho2O3, Ho(NO3)3, and Ho2(CO3)3; The Pr-containing compound is Pr6O 11 , Pr(NO3)3, Pr2(CO3)3; The Ca-containing compound is at least one of CaO, Ca(NO3)2, and CaCO3; The Mg-containing compound is at least one of MgO, Mg(NO3)2, and MgCO3; The Zr-containing compound is at least one of ZrO2, Zr(NO3)4, and Zr(CO3)2; The Gd-containing compound is at least one of Gd2O3, Gd(NO3)3, and Gd2(CO3)3; The Ga-containing compound is at least one of Ga2O3, Ga(NO3)3, and Ga2(CO3)3.
5. The preparation method according to claim 3, characterized in that: The sintering temperature of the high temperature solid phase method in step S1 is 1350-1500°C, and the sintering time is 36-60 h.
6. The preparation method according to claim 3, characterized in that: The annealing treatment in step S3 is performed at a temperature of 1200-1450° C. and for a time of 60-72 h.
7. The use of the mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal according to claim 1 or 2, characterized in that: The mid-infrared holmium-praseodymium-calcium-magnesium-zirconium co-doped gadolinium-gallium-garnet laser crystal is used to achieve mid-infrared laser output in the 2.7-3.1 μm band.
Citation Information
Patent Citations
Calcium-magnesium-zirconium-doped gadolinium-gallium garnet crystal, and preparation method, application and temperature field thereof
CN114250515A
Holmium-praseodymium co-doped scandium oxide mid-infrared band laser crystal and preparation method and application thereof
CN115261986A